Midline Household Survey Results: Rupandehi, Nepal - Bhusal, Aastha; Pudasaini, Roshan; Khatri, Laxman; Neupane, Santosh; Nagpal, Mansi; Khatri-Chhetri, Arun (2020)
This report summarizes the main findings from the household midline survey conducted in seven villages of the district of Rupandehi, one of CCAFS site, in Nepal in July 2019. The household survey revisited the 135 households of the 2012 CCAFS baseline survey and used the same standardized household survey tools. The Open Data Kit (ODK) software was used for the data collection.